Adeno-associated viral vector injection reduces adult hippocampal neurogenesis in mouse brain - Puumalainen, Veera (2023)
During adulthood, new neurons are mainly generated in hippocampal dentate gyrus. This process is known as adult hippocampal neurogenesis (AHN), during which neural progenitor cells divide, and mature into adult-born dentate granule cells. Finally they integrate into hippocampal networks, which are known to take part in learning and memory. Calcium imaging methods have permitted studying the cellular level events of learning and memory in vivo. For this, genes encoding for fluorescent calcium indicators are conveyed to neuronal cells, and when coupled with micro-optical tools they enable the live monitoring of calcium activity, reflecting activation of neurons. Adeno-associated virus (AAV) is one of the most used genetic vectors for calcium indicator expression on the target cells. AAVs are regarded as safe and effective, and so recombinant AAVs are developed increasingly to deliver transgenes to target tissues. However, recent research has revealed AAVs’ potency to induce cell death in many cell types, including neural progenitor cells and adult-born neurons. In this study, the AAV-induced effects on AHN were assessed by injecting saline (n=6) or AAV9 vector carrying GCaMP6s calcium indicator unilaterally to dentate gyri of adult male mice (n=10). After ca. 33 weeks, the number of adult-born neurons was determined bilaterally by doublecortin immunolabeling and confocal microscopy. In addition, the amount of GCaMP6s-derived green fluorescence (GF) was measured as a marker for transgene expression. Ipsilaterally to the injection, AAV reduced the number of adult-born neurons, i.e., neurogenesis, in comparison to saline-injected control group. The effect was local, since the number of new neurons in the contralateral hemisphere of AAV injected mice did not differ from control group. Surprisingly, no association between the GF intensity and the decrease of neurogenesis was found, and the reason for this lack of correlation remains unclear. In conclusion, this study shows the harmful effect of AAV on AHN and agrees with the scarce amount of existing data on this concern. This issue demands further research since AAVs are among the leading gene therapy vectors and research tools, also within central nervous system.